(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
In this article it has been said about the hospitality of two countries such as Uzbekistan and England and they are contrasted with cultural diversities. These cultures are not similar to their historical background so this factor is a great cause.